Neuroimaging and neuropathological findings in older adults with COVID‐19: A cognitive‐neuroscience systematic review to inform the long‐term impact of the virus on neurocognitive trajectories. (December 2021) - Manca, Riccardo; De Marco, Matteo; Ince, Paul; Venneri, Annalena
Abstract: Background: Infection due to Coronavirus Disease 2019 (COVID‐19) has been found to have detrimental effects on multiple body systems, especially in older adults. Acute neurological symptoms may be present and often associated with neural injuries. However, the long‐term consequences of COVID‐19 on neurocognitive functioning are still unknown. Therefore, this systematic review aims to summarise neuroimaging and neuropathological findings in patients with COVID‐19 aged ≥ 60 within a cognitive neuroscientific perspective, to clarify which brain areas may be more affected and the possible cognitive consequences. Method: Two databases (PubMed and Web of Science) were searched to identify all relevant manuscripts published between 1st March 2020 and 14th September 2020. The papers were screened and selected for inclusion by two independent assessors. Additional relevant studies not detected by the literature search were added manually. Result: A total of 74 studies were included. A wide variety of neural findings in older patients with COVID‐19 emerged from most studies, with a prominent role played by cerebrovascular damage. Structural and functional abnormalities were reported in all brain areas. The most consistent findings were observed in white matter, brainstem and fronto‐temporal areas. Moreover, viral DNA was also detected mainly in olfactory, orbitofrontal and brainstem areas. Conclusion: The vast literature on the link between COVID‐19 and neural damage is currently limited to the description of hospitalised patients who either had a fatal outcome or severe symptoms. The damage observed in this population seems acute and largely irreversible, mainly in neural regions involved in major functional cognitive networks. It is currently unknown whether the long‐term impact of COVID‐19 will be limited to the chronic evolution of acute events or whether novel mechanisms will emerge. Future theoretical frameworks describing the long‐term impact of COVID‐19 infection on mental abilities will have to factor in major trends of aetiological and topographic heterogeneity.